Properties of Fibreboard Made from Cultivated Leucaena leucocephala and Rubberwood - Ab. Rahman, Hilmi; Mohd Nazri Wan Abdul Rahman, Wan; Amalina Razali, Nur; Kasim, Jamaludin; Fitri Sa’ad, Muhammad; Japaruddin, Yani; Ogawa, Naoki (International Journal of Engineering and Technology, 2018)
Fibreboard made from cultivated Leucaena leucocephala  (3 and 5 year-old) and rubberwood has been prepared. Three wood ratios of Leucaena leucocephala/Rubberwood (20:80, 50:50 and 80:20) and three levels of resin content (15%, 18% and 20%) were the selected variations in this study. The objective of the study is to determine the physical and mechanical properties of fibreboard made from Leucaena leucocephala and rubberwood. Results showed that the mechanical properties of modulus of rupture (MOR), modulus of elastic (MOE) and internal bond (IB) exhibit an increasing trend along with the increment of Leucaena leucocephala percentage (20% to 80%) in the fibreboard. Mechanical and physical properties of the board made from 3 year-old Leucaena leucocephala and rubberwood shows positively enhancement with the increasing of resin content. Whereas, the enhancement of the mechanical properties of fibreboard made from 5 year-old Leucaena leucocephala and rubberwood was observed as the percentage ratio of Leucaena leucocephala increased. Both of fibreboard made from 3 and 5 year-old Leucaena leucocephala passes the minimum mechanical properties requirement of JIS A 5905: 2003 Fibreboard.